2021
DOI: 10.21037/atm-21-3823
|View full text |Cite
|
Sign up to set email alerts
|

miRNA-218/FANCI is associated with metastasis and poor prognosis in lung adenocarcinoma: a bioinformatics analysis

Abstract: Background: In this study, tumor microarray analysis was used to screen the key messenger RNAs (mRNAs) and microRNAs related to the progression of lung adenocarcinoma (LUAD), in order to provide a theoretical basis for early diagnosis, therapeutic targets, and prognosis evaluation of patients with LUAD. Methods:The mRNA and miRNA expression datasets came from the Gene Expression Omnibus (GEO) project database. Differentially expressed genes (DEGs) and microRNAs (DEMs) between LUAD tissues and adjacent lung tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…16-HBE cell line was obtained from the Basic Department of Chengde Medical College (Chengde, China). The cells were cultured in RPMI-1640 medium supplemented with 10% fetal bovine serum (Vivacell, Shanghai, China) and 1% penicillin/streptomycin (Invitrogen, Carlsbad, CA, USA) in a humidified 37 °C incubator with 5% CO 2 [ 13 ]. The cells (approximately 4 × 10 5 /well) were plated in six-well plates and incubated for 24 h [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…16-HBE cell line was obtained from the Basic Department of Chengde Medical College (Chengde, China). The cells were cultured in RPMI-1640 medium supplemented with 10% fetal bovine serum (Vivacell, Shanghai, China) and 1% penicillin/streptomycin (Invitrogen, Carlsbad, CA, USA) in a humidified 37 °C incubator with 5% CO 2 [ 13 ]. The cells (approximately 4 × 10 5 /well) were plated in six-well plates and incubated for 24 h [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Which may contribute to cancer cells' survival, and promote tumor cell resistance against radiotherapy and chemotherapy [10]. Besides, the functions of the FANCI protein have been investigated in various cancers, and FANCI has also been proven to be regarded as a prognostic biomarker, given its high expression is associated with poor survival rate and therapeutic outcome in lung adenocarcinoma, cervical cancer, and ovarian cancer [11][12][13]. However, there is currently a lack of studies on the relationship between the expression of FANCI and liver cancer.…”
Section: Ivyspringmentioning
confidence: 99%
“…FANCI is a potential biomarker for the prognosis of hepatocellular carcinoma [18]. A lot of relevant papers have also shown that the high expression of FANCI in tumors is closely related to the survival rate and poor prognosis of cancer patients, such as FANCI may interact with extracellular matrix receptors to affect the poor prognosis of lung adenocarcinoma [19] and pathogenic FANCI mutations increase the risk of familial ovarian cancer [20]. However, the reports of the mechanism of FANCI in glioma development and progression are still very few.…”
Section: Introductionmentioning
confidence: 99%